Sequential activation of the three protomers in the Moloney murine leukemia virus Env - Sjöberg, Mathilda (Proc Natl Acad Sci U S A, 2017)
Viral membrane fusion proteins of class I are trimers in which the protomeric unit is a complex of a surface subunit (SU) and a fusion active transmembrane subunit (TM). Here we have studied how the protomeric units of Moloney murine leukemia virus envelope protein (Env) are activated in relation to each other, sequentially or simultaneously. We followed the isomerization of the SU-TM disulfide and subsequent SU release from Env with biochemical methods and found that this early activation step occurred sequentially in the three protomers, generating two asymmetric oligomer intermediates according to the scheme (SU-TM)(3) → (SU-TM)(2)TM → (SU-TM)TM(2) → TM(3). This was the case both when activation was triggered in vitro by depleting stabilizing Ca(2+) from solubilized Env and when viral Env was receptor triggered on rat XC cells. In the latter case, the activation reaction was too fast for direct observation of the intermediates, but they could be caught by alkylation of the isomerization active thiol.